THE EFFECT OF THE APPLICATION OF THE PROBLEM BASED LEARNING MODEL ON THE RESULTS OF THE DOWN PASSING LEARNING IN VOLYBALL GAMES ON THE V CLASS STUDENTS OF SD NEGERI PENANGGAPAN 01 BREBES DISTRICT - Mahesta, Tio (Journal of Physical Education and Sport Science, 2024)
This research is motivated by the number of students who have not been able to do passing down volleyball, therefore there is a need for improvements in the learning model at SD Negeri Penangapan 01. The formulation of the problem in this study is whether there is an effect of the Problem Based Learning learning model on the learning outcomes of passing down the ball. Volleyball for fifth graders at Penanggapan 01. The purpose of this study was to determine the improvement in the learning outcomes of Lower Passing Volleyball for Fifth Grade Elementary School Students at Pen Responding 01 Elementary School.The research method used is a quantitative research method with the type of Pre-Experimental research model. The sample of this research is the fifth grade students of SD Negeri Peng Responding 01 using the purposive sampling technique. Method of data analysis using paired sample-t-test with a significant level of 5%.The conclusion of this research is that there is an increase in learning outcomes at the bottom through the Problem Based Learning learning model at SD Negeri Penanggapan 01 because in using this learning model students are given the freedom to learn